Immunohistochemical expression of interleukin-2 receptor and interleukin-6 in patients with prostate cancer and benign prostatic hyperplasia: Association with asymptomatic inflammatory prostatitis NIH category IV. (April 2014) - Engelhardt, Paul Friedrich; Seklehner, Stephan; Brustmann, Hermann; Lusuardi, Lukas; Riedl, Claus R.
Abstract: Objective. This study prospectively investigated the immunohistochemical expression of interleukin-2 receptor (IL-2R) and interleukin-6 (IL-6) in patients with prostate cancer and benign prostatic hyperplasia (BPH), and a possible association of these conditions with asymptomatic inflammatory prostatitis National Institutes of Health (NIH) category IV. Materials and methods. The study included 139 consecutive patients who underwent transurethral resection of the prostate and transvesical enucleation of the prostate ( n = 82) or radical prostatectomy ( n = 57). To characterize inflammatory changes the criteria proposed by Irani et al. [J Urol 1997;157:1301–3] were used. IL-2R and IL-6 expression was studied by a standard immunohistochemical method. Results were correlated with tumour, node, metastasis stage, Gleason scores, total prostate-specific antigen, International Prostate Symptom Score and body mass index. Results. IL-2R and IL-6 expression was significantly higher in neoplastic prostate cancer tissue than in normal tissue of prostate cancer patients ( p < 0.001 and p < 0.04, respectively). Prostate cancer patients with prostatitis showed significantly higher IL-2R expression than those without inflammation ( p < 0.03). In patients with BPH, expression of IL-2R as well as IL-6 was higher in patients with prostatitis than in those without ( p < 0.01 and p < 0.02, respectively). Conclusions. IL-2R and IL-6 expression was significantly higher in prostate cancer tissue than in normal tissue. Patients with asymptomatic inflammatory prostatitis NIH category IV showed significantly greater activity.